SOIL SEED BANK GERMINATION IN PINE FORESTS AND SHRUBS, IN GUNUNG CIREMAI NATIONAL PARK - Toto Supartono; Ilham Adhya; Bambang Yudayana (Journal of Forestry And Environment, 2018)
Problems that often occur in ecosystem restoration through planting are stem and root damage, plant death, and high costs. One possible solution is to trigger the germination of soil seed banks. The purpose of this study was to analyze the germination of soil seed banks in shrubs and pine stands, Gunung Ciremai National Park. The method used was soil sampling and sample plots. The results of the study provided evidence that pioneer tree germination did not occur, both in bushes and in pine stands. Germinated woody species was calliandra with densities 8.53 individuals/m2 (bush) and 5.74 individuals/m2 (pine stands) for sample plots and 3.15 individuals/tray (bush) and 4.03 individuals/tray (pine) for the soil sampling. The density of the calliandra between the two types of cover was not different (p = 0.123 for the sample plot method; and p = 0.452 for the soil sample method).  The absence of pioneer species germination indicated that the restoration of ecosystems must be planted.